Words into deeds: the use of framing strategy in EU higher education policy - Serrano-Velarde, Kathia (Critical policy studies, 2014)
This article offers an analysis of the framing strategy of EU policymakers within the framework of the open method of coordination (OMC). It argues that the institutional embeddedness of agents has an impact on the way policy ideas are framed and maintained over time. The study interprets a multi-method, qualitative research project that analyzes the evolution of European Union higher education policy from 2000 to 2011, a period in which the introduction of the OMC brought about drastic changes, making higher education, once a highly contested policy field, a cornerstone of the Lisbon Agenda. By combining framing theoretical insights with neo-institutional theory, we show that the framing strategy adopted by policy agents in the European Commission operates in two ways: first, the strategic adoption of frames increases the visibility of the higher education agenda at the European level and second, it serves as a means to take action in politically opportune circumstances, thereby paving the way for the development and implementation of new programs.
Gesehen am 25.09.2017